1-(4-Cyanophenyldiazen-2-ium-1-yl)-2-naphtholate - Yan-Hong Yu; Kun Qian (Acta Crystallographica Section E, 2009)
In the molecule of the zwitterionic title compound, C17H11N3O, the naphthalene ring system is planar [maximum deviation = 0.029 (3) Å] and is oriented at a dihedral angle of 3.55 (3)° with respect to the benzene ring. An intramolecular N—H...O hydrogen bond results in the formation of a planar six-membered ring. In the crystal structure, intermolecular C—H...O interactions link the molecules into centrosymmetric dimers.